2010
DOI: 10.1017/s1461145710000349
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous projections from prefrontal cortex to dopaminergic and serotonergic nuclei

Abstract: Derangements of the prefrontal cortex (PFC) and of brainstem monoaminergic systems occur in depression and schizophrenia. Anatomical and functional evidence supports a PFC control of the brainstem monoaminergic systems. Similarly, the PFC contains a high density of monoamine receptors for which antipsychotic drugs exhibit high affinity. This raises the possibility that pathological or drug-induced changes in PFC may subsequently alter monoaminergic activity. Recent data indicate that a substantial proportion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 76 publications
2
24
0
Order By: Relevance
“…DAVID categorized these genes into those controlling lipid metabolism, coagulation, hormonal activity, immunological function, and amine synthesis, with significant interactions among each categorized gene. The PFC is a projection area for dopaminergic and serotonergic neurons and modulates these systems [4345]. For instance, Tryptophan 2,3-dioxygenase (Tdo2) was categorized as an amine synthesis molecule by DAVID in this study, and it is a rate-limiting enzyme expressed in the pathway from tryptophan to kynurenine, which is an alternative pathway to the tryptophan-serotonin pathway [15].…”
Section: Discussionmentioning
confidence: 99%
“…DAVID categorized these genes into those controlling lipid metabolism, coagulation, hormonal activity, immunological function, and amine synthesis, with significant interactions among each categorized gene. The PFC is a projection area for dopaminergic and serotonergic neurons and modulates these systems [4345]. For instance, Tryptophan 2,3-dioxygenase (Tdo2) was categorized as an amine synthesis molecule by DAVID in this study, and it is a rate-limiting enzyme expressed in the pathway from tryptophan to kynurenine, which is an alternative pathway to the tryptophan-serotonin pathway [15].…”
Section: Discussionmentioning
confidence: 99%
“…Lower abundances are found in ventro-caudal part of CA3, medial mammillary nucleus, striatum (dorsal and ventral) and several brainstem nuclei (Pompeiano et al, 1994; Burnet et al, 1995; López-Giménez et al, 1998). Interestingly, pyramidal neurons in the rat PFC that simultaneously project to the ventral tegmental area and the dorsal raphe nucleus express 5-HT 2A receptors (Vázquez-Borsetti et al, 2009, 2011). This reveals a close anatomical interaction or “loop” between frontal areas and dopamine and serotonin neurons of the brainstem, as found in several electrophysiological studies (Thierry et al, 1979, 1983; Tong et al, 1996; Hajós et al, 1998; Celada et al, 2001; Martín-Ruiz et al, 2001).…”
Section: The Cortical 5-ht System: Receptor Localizationmentioning
confidence: 99%
“…The neocortex contains low levels of the 5-HT 4 receptor and its encoding mRNA, as assessed by autoradiography and in situ hybridization, respectively (Waeber et al, 1994; Vilaró et al, 1996, 2005). However, studies using single-cell RT-PCR technique reported that ~60% of pyramidal neurons recorded in the PFC contain the 5-HT 4 receptor transcript (Feng et al, 2001), and overexpression of 5-HT 4 in the mPFC increases DRN 5-HT activity (Lucas et al, 2005) likely through descending excitatory axons reaching the DR (Celada et al, 2001; Vázquez-Borsetti et al, 2011). …”
Section: The Cortical 5-ht System: Receptor Localizationmentioning
confidence: 99%
“…A small population of PFC neurons may be responsible for this output, as individual neurons within the PFC innervate more than one neuromodulatory center. For instance, a small population of PFC neurons project to both the RN and the VTA (Gabbott et al, 2005; Vázquez-Borsetti et al, 2009, 2011). Similarly, a subset of PFC neurons project to both RN and LC (Lee et al, 2005).…”
Section: Neuromodulation and The Prefrontal Cortexmentioning
confidence: 99%